Verbal fluency tasks: effects of age, gender, and education - Nogueira, D. S.; Reis, E. A.; Vieira, A. (Folia Phoniatrica et Logopaedica, 2016)
Objectives: This study presents data for semantic fluency, phonemic fluency, action fluency, and alternate fluency. The aim is to provide normative data by age, gender, and education for European Portuguese in each fluency category. Methods: Norms for the verbal fluency task were collected from a volunteer population of 444 healthy Portuguese participants. Multiple regression analysis with age, gender, and education as independent variables was performed for the semantic fluency global score, and these variables were considered separately for each phonemic category. Results: Age, education, and gender significantly affected the semantic global score, as well as scores of names, supermarket, kitchen objects, food, and clothes. No gender effect was observed in the categories "p-words," animals, transports, verbs, and alternating fluency. This last category was only influenced by years of education. Conclusions: Equivalent scores of verbal fluency tasks are useful in clinical practice, allowing the comparison between the normal and the abnormal performance of language disorders.